The inhibitory effect of turmeric curcuminoids on matrix metalloproteinase-3 secretion in human invasive breast carcinoma cells - Mathanaporn Boonrao (2018)
Matrix metalloproteinase-3 (MMP-3) is a key enzyme with important implications in the invasion and metastasis of breast cancer cells. Curcumin (Cur), demethoxycurcumin (DMC), and bisdemethoxycurcumin (BDMC) are major forms of curcuminoids found in turmeric powder with reported anticancer activity. This study focuses on the comparative effect of Cur, DMC and BDMC on the modulation of MMP-3 activity and its secretion in MDA-MB-231 breast cancer cells. MMP-3 levels were determined by casein zymography, ELISA and western blotting. Analysis of MMP-3 expression by casein zymography revealed high expression in MDA-MB-231 invasive breast carcinoma cells, but not in MCF-7 non-invasive breast cancer cells. ELISA assays showed MMP-3 levels were significantly decreased in all curcuminoid treatments. Using zymography, treatment with non-toxic doses revealed that every curcuminoid compound except Cur reduced MMP-3 levels. Moreover, the result from western blot analysis confirmed that only DMC and BDMC reduced MMP-3 secretion in MDA-MB-231 cells, but Cur did not have any effect. MMP-3 activity revealed that none of the curcuminoids showed significant effects. However, treatment of the cells with Cur, DMC and BDMC exhibited a significant inhibition of cell invasion and motility with DMC and BDMC being more potent. These results suggest that Cur, DMC, and BDMC may be used as MMP-3 inhibitors to modulate MMP-3 expression. © 2010 The Pharmaceutical Society of Korea and Springer Netherlands.